Center-Pivot-Irrigated Grain Sorghum Cost-Return Budget - Dumler, Troy J.; O'Brien, Daniel M. (My University, 1998)
This publication projects a budget that reflects expected income and costs based on center-pivot-irrigated grain sorghum production in Kansas.
MF582_1998_10
Keywords: MF582; Economics; Crops; MF